OPEN SOURCE SEBAGAI BENTUK PERLAWANAN TERHADAP KAPITALIS MEDIA BARU - N. Agung Wardjito Ardhoyo (Jurnal Komunikasi & Media Digital, 2023)
Using the internet and various digital products will improve the economy of the people and the country. But on the other side is possibility of piracy activity. This is based on the characteristics of digital communication in the new media era. Various forms of piracy in the digital era are seen as damaging network order, and are even considered to have undermined state authority. Governments and capitalists are always trying to rewrite the rules. They marginalize online products as public property and support private ownership and commercial interests. But the cases of digital piracy never end. So efforts to maintain the exclusivity based on the ability to pay seem to be in vain. This paper aims to provide insight into how Open Source (OS) or Open Access (OA) works. So that answers what the moral purpose to be conveyed in the activity. The method in this paper uses a critism paradigm with a qualitative approach. The data obtained through observation, documentation and interviews. For the conclusion from this paper, there are various reasons why piracy occurs. Open Source or Open Access is the right route to end piracy.